An umbrella review of systematic reviews of β‐hydroxy‐β‐methyl butyrate supplementation in ageing and clinical practice. Issue 5 (12th July 2022) - Phillips, Stuart M.; Lau, Kyle J.; D'Souza, Alysha C.; Nunes, Everson A.
Abstract: The compound β‐hydroxy‐β‐methyl butyrate (HMB) is proposed to increase or mitigate the loss of skeletal muscle and improve muscle function. We undertook a review of systematic reviews of HMB supplementation to promote gains or mitigate muscle loss in ageing and clinical populations. Following PRISMA guidelines, we searched for systematic reviews reporting the effect of HMB in our target populations. Dual‐energy X‐ray absorptiometry (DXA) measured lean soft‐tissue mass (LSTM) was accepted as a proxy for muscle. We identified 15 systematic reviews that met our inclusion criteria, which were independently evaluated. The methodological quality of the reviews was assessed using A Measurement Tool to Assess Systematic Reviews (AMSTAR), and standardized effectiveness statements were generated. Five of 15 studies found some evidence that HMB augmented LSTM; the remaining 10 studies reported some evidence favouring no difference (6/10 studies) or insufficient evidence to determine an effect (4/10 studies). Of the 12 studies that evaluated strength, 4/12 found some evidence, 5/12 found some evidence of no effect with one article finding some evidence in favour of patients in peri‐hospitalized and no evidence for those that are community‐dwelling, 4/12 had insufficient evidence to determine an effect, and 1/12 had insufficient evidence. No]study reported a positive effect of HMB on physical function; however, 2/10 studies found some evidence favouring no effect, and 7/10 studies reported insufficient evidence to determine an effect. The effectiveness of HMB supplementation in augmenting LSTM was heterogeneous, with most reviews finding no effect or inconclusive evidence to determine an effect. Most reviews concluded that HMB supplementation did not affect strength outcome measures or studies were inconclusive. The current evidence is insufficient to assess the impact of HMB supplementation on functional outcome measures. Our analysis shows minor, inconsistent support for HMB as part of an oral nutritional supplement or as a stand‐alone supplement (or combined with other amino acids) to increase or promote retention of LSTM, improve strength, and no evidence that it improves physical function in older persons or clinical populations.